HEART DISEASE AND SOCIAL INEQUALITY: ETHICAL ISSUES IN THE AETIOLOGY, PREVENTION AND TREATMENT OF HEART DISEASE - Boddington, Paula (Bioethics, 2009)
Heart disease is a complex condition that is a leading cause of death worldwide. It is often seen as a disease of affluence, yet is strongly associated with a gradient in socio-economic status. Its highly complex causality means that many different facets of social and economic life are implicated in its aetiology, including factors such as workplace hierarchy and agricultural policy, together with other well-known factors such as what passes for individual ‘lifestyle’. The very untangling of causes for heart disease thus inevitably raises social, moral and political issues. These include the proper role of the individual and of larger social forces in its aetiology, prevention and treatment. The construction of risk factors for heart disease likewise is enmeshed with questions of distributive justice in the responsible targeting of those at risk for heart disease, a debate which has received much overt attention in the medical literature, but less attention within the ethical literature. Strategies for addressing a condition of such complex causality can be highly diverse, from pharmaceutical to social interventions, and value issues attach to the choice and presentation of such strategies. For example, prevention strategies may raise complex issues of responsibility and of judgements of what it is to ‘live well’. Further ethical debate on this highly political disease would be welcome.